PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DENGAN MODEL PROBLEM POSING UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN BIOLOGI SISWA KELAS X.2 SMA NEGERI 2 KARANGANYAR TAHUN PELAJARAN 2011/2012 - Suparmi, Suparmi; Suciati, Suciati; Harlita, Harlita (P Biologi FKIP UNS Surakarta, 2013)
ABSTRACT ? This research aims to improve low quality of biology in class X.2 SMA Negeri 2 Karanganyar in academic year 2011/2012. Learning considered by teacher?s performance, utility of facilities in the classroom, classroom climate, student?s scientific attitude, and student motivation of achievement applying for approach Contextual Teaching and Learning with Problem Posing model. This research was a classroom action research which and performed in three cycles. Each cycle consisted of 4 phases, namely planning, action, observation, and reflection. The data was collected Tes and Non Tes by question, questionnaire, observation, and manual interview. Data validation was used triangulation of methods and triangulation of observers. The obtained data were analyzed using descriptive technique. The results of this research showed that according triangulation the average percentage for teacher?s performance in pre cycle (60%), cycle I (86,67%), cycle II (96,67%) and cycle III (100%); classroom climate pre cycle (54,16%), cycle I (68,05%), cycle II (76,38%) and cycle III (86,80%); student?s scientific attitude pre cycle (50,92%), cycle I (65,27%), cycle II (74,07%) and cycle III (83,79%); and student motivation of achievement pre cycle (57,71%), cycle I (65,75%), cycle II (74,38%) and cycle III (85,80%); utility of learning facilities in the classroom have been optimally. The results showed that the average percentage quality of biology learning aspect such as pre cycle (55,69%), cycle I (71,43%), cycle II (80,37%) and cycle III (89,09%) (increase 33,4% from pre cycle to cycle III). Cycles stopped in cycle III because the research target is achieved. The conclusion of this research describes that the implementation of approach contextual teaching and learning with problem posing model can improve quality of biology learning considered by teacher?s performance, utility of facilities in the classroom, classroom climate, student?s scientific attitude, and student motivation of achievement in class X.2 at SMA Negeri 2 Karanganyar in academic year 2011/2012. Keywords: Contextual teaching and learning, Problem posing, Quality of biology Learning